LIMITATION OF RIGHTS AS A MANIFESTATION OF DUTIES AND RESPONSIBILITIES PERTAINING TO THE FREEDOM EXPRESSION IN DIGITAL COMMUNICATIONS - Makarim, Edmon; Brata, Muhammad Ibrahim; Arsyafira, Nabilla (UI Scholars Hub, 2019)
The freedom of expression is thriving due to the global use of the internet. The digital era has revolutionized the scope, practices, and even the definition of freedom expression. However, it also evokes a number of social concerns. Offenses such as the circulation of defamation, hate speech, misleading propaganda to the masses, and fraud, for instance, can be found in the internet. Certain limitations deriving from the conditions prescribed by the human rights principles and instruments as well as the national constitution are therefore prudent to prevent the excess of freedom. As a state that abides to the rule of law, Indonesia recognizes the freedom of expression as a manifestation of human rights that is crucial to democracy. While new laws such as the Information and Electronic Transaction Act have been enacted to answer the challenges brought by the digital era upon the freedom of expression, the question of whether the existing laws have accommodated an ideal balance between restriction and protection for the freedom of expression remains a matter worth reviewing. This paper aims to study the limits of the freedom of expression, particularly in the digital context, in the constellation of the Indonesian legal system and how they converge and correlate with one another. Finally, this study concludes that the Indonesian government must protect its citizens from the spread and use of illegal content in electronic communications by enforcing and harmonizing its criminal, private, and administrative law configurations.